A review on liquid chromatographic methods for the bioanalysis of atorvastatin - Karan Wadhwa; A. C. Rana (SpringerOpen, 2021)
Abstract Background The unsatisfied clinical need has encouraged the development and validation of bioanalytical procedures for the quantification of drugs in biological samples because the monitoring of drug concentrations helps in personalizing the patient's pharmacotherapy, assessing the adherence to therapy, and is also extensively useful for pharmacokinetics and drug-drug interactions studies. Main Body The present review aimed to provide insightful information about the various liquid chromatographic methods developed till 2019 for the analysis and quantification of atorvastatin, its metabolites, and co-administered drugs in the various biological matrices like the serum, plasma, and urine with special emphasis on sample preparation techniques applied before chromatographic analysis along with different chromatographic conditions and their validation data. A total of 88 published papers that have used liquid chromatography techniques to quantify atorvastatin in biological fluids are included in the study. Out of the total reported liquid chromatographic methods, 34% used UV spectrophotometer as a detector, and 55% used MS/MS as a detector. Whereas 38% of them used protein precipitation procedure, 33% applied liquid-liquid extraction approach, and 12% employed solid-phase extraction technique for sample preparation. Conclusion In the last decade, numerous bioanalytical procedures have been developed for the quantification of atorvastatin in different biological samples using liquid chromatographic techniques. Moreover, advancement in technology developed several new and advanced sample preparation approaches like dispersive liquid-liquid extraction, microextraction by packed sorbent, which have high recovery rates than conventional procedures. Thus, the summarized review may be consulted as an informative tool to support the optimization of new bioanalytical methods for the quantification of atorvastatin.